Coaching the discus - Pagani, Tom; Coaches Choice (Monterey, CA : Coaches Choice, 2002)
Explain and demonstration of the learning sequences and practical drills that can be used to help both the coach and the athlete better understand how to throw the discuc properly
Keywords: Discus throwing; Sports